Fundamentals of Entrepreneurship ETR300 : Global Telecommunication Enterprise / Suryati Sahari... [et al.] - Sahari, Suryati; Andrew Uni, Shanty Jata; Mohd Leo, Mastura; Martin, Leslie Luther (2007)
In every progressive firm or organization, top management is very important to responsible for setting quantifiable, measurable and attainable objectives. This is to make sure the top management of the company can achieve the goal as their state before. In our company Global Telecommunication, our policy is developed as a guideline for daily operation of the company that stresses more on the continual need to maximize profits in a just reasonable manner. Apart from trying to earn a fair return on investment from our stockholders. Other than date, we also are looking forward to improve our share in the market size. In addition, we will try to providing our customer with the best services to ensure our customers really Satisfied with our company. However, to achieve our objective, we had determined our target market. Based on our research, we have more than three competitors, such as, Hotlink Mighty Communication Branch, Three Star Telecommunication, Choo Brothers & Company and so on. So our target market we was share with the other competitors. Overall our target markets are mostly among the residents in Kota Samarahan. As the new company we will try the best.